Real-World Lenvatinib Versus Sorafenib in Patients With Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis - Kuo, Yuan-Hung; Lu, Sheng-Nan; Chen, Yen-Yang; Kee, Kwong-Ming; Yen, Yi-Hao; Hung, Chao-Hung; Hu, Tsung-Hui; Chen, Chien-Hung; Wang, Jing-Houng (Frontiers in Oncology, 2021)
Background Lenvatinib is approved for patients with advanced hepatocellular carcinoma (HCC) due to its non-inferiority to sorafenib of overall survival (OR) in clinical trials. This study was to compare the effectiveness and safety of lenvatinib and sorafenib in the real world. Methods We retrospectively evaluated 338 patients with unresectable HCC who had undergone lenvatinib or sorafenib treatment between January 2018 and August 2020. Propensity-score matching analysis was performed with a 1:2 ratio to reduce the real-life baseline difference between the two groups. Results A total of 210 patients (Male/Female: 150/60, mean age: 65.8 years) were recruited including 70 patients in the Lenvatinib group and 140 patients in the Sorafenib group. Compared with sorafenib, lenvatinib had significantly longer progression-free survival (PFS) (5.2 vs 3.3 months, p=0.019) but similar OR (13.3 vs 11.8 months, p=0.714). Additionally, lenvatinib had better disease control rates (62.3 vs 48.6%, p=0.029) and equivalent incidences of treatment-related adverse events over sorafenib. In multivariate analysis, lenvatinib was associated with better PFS over sorafenib (hazard ratio: 0.49, 95% confidence interval: 0.3–0.79, p=0.004) after adjustments of albumin-bilirubin grade and alpha-fetoprotein level; however, different agents using lenvatinib or sorafenib did not contribute to OS, whether in univariate or multivariate analysis. Patients who failed lenvatinib had a lower proportion of having sequential systemic therapies compared with the Sorafenib group (36.2 vs 47.8%, p=0.02). The most frequently used sequential therapy following lenvatinib and sorafenib was chemotherapy (n=9, 42.8%) and regorafenib (n=33, 50.8%), respectively. Conclusions In clinical real-life practice, lenvatinib illustrated promising survival benefits and acceptable safety for patients with unresectable HCC, while reducing the risk of progression disease compared with sorafenib. Additionally, lack of approved post-lenvatinib systemic therapies is a serious issue in the real world.